The Pharyngeal Airways of Patients with Class II Malocclusion: A Cone-Beam Computed Tomography Analysis - Ay Ünüvar, Yazgı; Bilgiç Zortuk, Fundagül; Özer, Törün; Beycan, Kadir (UI Scholars Hub, 2021)
Background: This study aimed to compare the minimum axial (min Ax) area and the volumes of the nasopharyngeal (NP) and oropharyngeal (OP) airways of patients with Class II malocclusion with different sagittal positions of the mandible and maxilla and patients with Class I malocclusion with normal jaw positions. Methods: Airway areas and volumes of 51 patients with Class I malocclusion with normal maxillary and mandibular positions (0 < ANB < 4, 84 > SNA > 80, and 82 > SNB > 78) were compared with 21 patients with Class II malocclusion with normal maxillary and retrognathic mandibular positions (ANB>4, 84>SNA>80, and SNB4, SNA>84, and 82>SNB>78). Results: In the comparison of airway measurements between Class I and Class II groups, significant differences were found in the OP airway volume, total airway volume, and minimum OP axial area. Patients with Class II mandibular retrusion had smaller OP airway volume. The total airway volume and min Ax area were significantly lower in the Class II mandibular retrusion group than in other groups. Conclusions: The sagittal position of the jaws affects the OP airway volume and the minimum axial airway area, but not the NP airway volume.